Age- and sex-specific risk of colorectal cancer in incident ulcerative colitis during the first 10 years after diagnosis: a nationwide population-based study. (2nd November 2021) - Kim, Hee Man; Kim, Ji Hoon; Lee, Jung Kuk; Kang, Dae Ryong; Kim, Hyunil; Kim, Su Young; Kim, Hyun-Soo
Abstract: Objective: We assessed the risk of colorectal cancer (CRC) in patients with ulcerative colitis (UC) using the nationwide population-based claims data. Materials and methods: We analyzed the claims data of the Korean National Health Insurance (2006–2015). UC and CRC were defined using ICD-10 codes and UC-specific prescriptions in this study. Age- and sex-matched individuals without UC were randomly selected from the general population. Hazard ratios (HRs), adjusted for different covariates, were calculated using multivariate Cox proportional hazard regression. Results: In total, 30, 546 and 88, 829 individuals with and without UC, respectively, were enrolled. CRC developed in 85 (0.27%) among UC, and 340 (0.38%) among individuals without UC, respectively. The HR (95% confidence interval [CI]) of CRC in all UC patients was 0.74 (0.58–0.94). Further, UC patients were stratified according to sex (male vs. female: 0.60 [0.44–0.82] vs. 1.10 [0.75–1.61]) and age (HR = 14.37, 2.74, 0.58, and 0.70 for 0–19, 20–39, 40–59, and ≥60 years, respectively). HR was significantly higher for late-onset UC (≥60 years) than for early-onset UC (0–19 years). The long duration of 5-aminosalicylic acid use had a significantly low HR, with reference to the 1st quartile. Conclusions: The risk of CRC varies with age and sex in Korean patients with UC during the first decade after diagnosis. Early-onset UC (<40 years) increases the CRC risk.